Pemeliharaan Larva Ikan Jelawat (Leptobarbus hoevenii) dengan Suhu Berbeda terhadap Kinerja Pertumbuhan dan Kelangsungan Hidup - Muhammmad Ikhwan Ihtifazhuddin; Ela Susi Febriyanti; Isriansyah Isriansyah; Komsanah Sukarti (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2026)
This study aims to analyze the effect of different maintenance media temperatures on the survival and growth of eel larvae (Leptobarbus hoevenii), and to determine the optimal temperature for larval growth. The study was conducted at the Experimental Pond Laboratory of the Faculty of Fisheries and Marine Sciences, Mulawarman University for 30 days using a Completely Randomized Design (CRD) with four temperature treatments, namely P1 (environmental temperature), P2 (28±1°C), P3 (30±1°C), and P4 (32±1°C), each with three replications. The parameters observed included survival rate, total length growth, absolute weight growth, and specific growth rate (SGR). The results showed that different temperatures did not have a significant effect (P>0.05) on the survival and total length growth of larvae, but had a significant effect (P<0.05) on absolute weight growth and SGR. The survival rate of larvae in all treatments reached 100%. The best growth was achieved in treatment P3 (30±1°C), which produced an average total length growth of 44.71 mm, an absolute weight of 1.85 g, and a SGR of 12.95%/day. These results indicate that 30°C is the optimal temperature for supporting efficient growth of eel larvae.